Air and surface temperatures from mount Elbrus East summit area, Caucasus, 5620 m a.s.l., and surface and ground temperatures at fumarolic field, 2013-2015, thermistor measurements (iButton and Hobo) - Andrey Abramov; Ivan I Lavrentiev; Stanislav S Kutuzov (PANGAEA, 2017)
The dataset represents temperature conditions of mount Elbrus East summit area. Two sites were organized: one at fumarolic field with sensors (iButton DL1922) on the surface at 0.05 cm depth and at 0.4 m depth, second at the rock nearby to represent natural conditions without volcanic influence with air (2 m height) and surface (0.05 m depth) sensors (Hobo U12-008 with TMC-HD sensors). Dataset covers July 2013 - July 2015, with some gaps due to air sensor damage. The MAST temperature out of fumarolic field is close to -16°C, and one at fumarolic field is close to 25°C.